The Role of Discipline, Motivation, and Job Satisfaction in Strengthening Human Capital for the Digital Economy - Muhammad Iqbal Fakih Nur Amni; Fahmi Kurniawan; Tri Bodroastuti; Retno Ginanjar; Wenny Ana Adnanti (IECON: International Economics and Business Conference, 2025)
This study aims to analyze employee performance in term of work discipline, motivation, and job satisfaction at PT Asuransi Central Asia and its subsidiaries, Consolidated Semarang. The primary focus is to evaluate how these three factors contribute to strenghthening human capital in the context of digital transformation. A descriptives research method was employeed, involving a total population 40 respondents selected using a saturated sampling technique. The findings reveal that employees demonstrate a strong awarnees of the importance of work discipline and consistently apply it in their daily tasks. Moreover, the motivtion provided by the company is perceived as adequated and positively influences job satisfaction. Job satisfaction is found to meet both qualitative and quantitative standards, ultimately enhancing individual and organizational performance. There result highlight that work discipline, motivation, and job satisfaction are essential components in optimizing human capital to meet the challenges and seize opportunities in the evolving.